Pengaruh Atribut Produk Herbal Terhadap Kepuasan Pelanggan - Sad, Raden Irwan; Sukartaatmadja, Iswandi (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Given the company's product attributes can know how much the level of customer satisfaction the company's products. To that end, the company has its own unique way and in a typical product attributes that customers will feel satisfied when buying products. Marketing activities can be done by improving and providing innovation to the product will be in production. Where products are manufactured must have a good product attributes in accordance with customer expectations, and creating customer satisfaction. This study aims to know the attributes of Herbal Products manufactured by Raudhoh. To find out the customer satisfaction in taking Herbal Products from Raudhoh. To determine the effect of product attributes on customer satisfaction Herbal Products Brand Raudhoh Raudhoh on international companies. The results showed the customer satisfaction of international raudhoh herbal products is 9.781. The calculated value of the correlation coefficient of 0.676 is obtained which means that there is a significant relationship with the closeness of the relationship strong and positive relationship between product attributes to customer satisfaction. the results obtained from the coefficient of determination 0.457, which means that the community has a contribution of 45.7% in creating customer satisfaction, and the rest is influenced by other factors Keywords: product attributes, customer satisfaction